PENGARUH GOOD CORPORATE GOVERNANCE DAN BIAYA OPERASIONAL DAN PENDAPATAN OPERASIONAL (BOPO) TERHADAP STABILITAS KEUANGAN BANK UMUM SYARIAH DI INDONESIA TAHUN 2012-2017 - Lucky Nugroho; Herda Nezzim Bararah (Politeknik Negeri Bengkalis, 2018)
This study aims to determine the impact or influence of good corporate governance and efficiency, which in this case the proxy by the ratio of operational costs and operating income to the financial stability of sharia commercial banks. The method in this research is a literature review or conceptual paper. Based on the results and review literature, it is known that the financial stability of sharia banks is a significant factor in maintaining reputation. Good corporate governance, operational costs, and operating income (BOPO) are factors that can support the financial stability of sharia commercial banks and in this study measured by Z-score. Therefore, financial stability in sharia banks should be the focus of the management of sharia commercial banks.